PENGARUH MOTIVASI KERJA TERHADAP PENINGKATAN KINERJA APARATUR SIPIL NEGARA DI KANTOR KELURAHAN MANISA KECAMATAN BARANTI KABUPATEN SIDENRENG RAPPANG PROVINSI SULAWESI SELATAN - Kamaruddin Sellang; Muh Darman (AkMen JURNAL ILMIAH, 2017)
This study aims to determine the influence of motivation to work toward improving the performance of civil state apparatus at the Village Office Manisa, District Baranti, Sidenreng Rappang and to determine the factors that affect the work motivation of civil state apparatus at the Village Office Manisa, District Baranti, Sidenreng Rappang. The design study is a quantitative approach. Research carried out for two months starting in June s.d August 2016. The population was taken from a board member of the Institute for Community and Environment in the Village Head of Manisa as many as 48 people. The samples using the total sample or samples saturated as many as 48 people. Data collection techniques used were observation, questionnaires, interviews, and literature. Data analysis technique used is quantitative descriptive Likert scale and assisted with SPSS. The results showed that motivation significantly influence the performance of the F-count value obtained at 23.269 with a probability level of sig. 0.000 (sig <0.05), which means that work motivation variable (X) has a significant influence on the performance (Y). Great influence on the performance of work motivation civilian state apparatus at the Village Office Manisa, District Baranti, Sidenreng Rappang 33.6% included in the criteria is not good. The factors that most affect the work motivation is the level of education that has contributed a percentage of 88.8% is included in the criteria very well, and for factors that have the lowest contribution that flexible regulation which only contributes a percentage of 53.6% is included in the criteria less well, so that the average percentage score of 71.6% included in bothcriteria.